The development and use of GIS database for the study of migratory birds in Kuala Gula National Park - Lum, Karen (2005)
Migratory birds are one of the living organisms that should be protected. These birds from northern hemisphere fly as far as 26 000 km a year across the continent for survival during the winter season. In addition, the migratory birds have consistently stopped by at Malaysia during the roosting season from November to March every year because they are attracted to the richness of Matang Mangrove Forest. The Department of Wildlife and National Parks (Kuala Gula) has carried out observation on the arrival of these migratory birds. The process of data collection had started since 1993, however, there is still no analysis had been carried out on the trend of bird migration for the past decade. The aim of this study is to develop a GIS database for the Department of Wildlife and National Parks (Kuala Gula) in order to facilitate the study of biodiversity and sustainability of migratory birds. Meanwhile, the objectives of this study is to find out the requirement of Department of Wildlife and National Park (Kuala Gula) ; build a GIS database for the migratory birds and performed analysis on the observed data. The methodology flows from need assessment to data collection, database development and system integration, and finally results and analysis on trend of bird migration, ecosystem properties, environment sensitivity analysis, morphometrics analysis and spatial statistic analysis on the distribution of the migratory birds. Database for managing biodiversity and sustainability of migratory birds has been developed using ArcView 3.2, MapObject 2.0, Microsoft Visual Basic 6.0, AutoCadMap 2.0 and S-Plus 2000. The result is a migratory bird’s database with statistical results on the trend of bird migration. From the results of trend of bird migration, the endangered species of migratory birds can be identified. Subsequently, from the endangered species being classified, it can provide guidelines and procedures in maintenance of the mangrove areas.